Cardiomyocyte Deletion of Bmal1 Exacerbates QT- and RR-Interval Prolongation in Scn5a+/ΔKPQ Mice - Schroder, Elizabeth A.; Wayland, Jennifer L.; Samuels, Kaitlyn M.; Shah, Syed F.; Burgess, Don E.; Seward, Tanya; Elayi, Claude S.; Esser, Karyn A.; Delisle, Brian P. (Frontiers in Physiology, 2021)
Circadian rhythms are generated by cell autonomous circadian clocks that perform a ubiquitous cellular time-keeping function and cell type-specific functions important for normal physiology. Studies show inducing the deletion of the core circadian clock transcription factor Bmal1 in adult mouse cardiomyocytes disrupts cardiac circadian clock function, slows heart rate and prolongs the QT-interval at slow heart rates. This study determined how inducing the deletion of Bmal1 in adult cardiomyocytes impacted the in vivo electrophysiological phenotype of a knock-in mouse model for the arrhythmogenic long QT syndrome (Scn5a+/ΔKPQ). Electrocardiographic telemetry showed inducing the deletion of Bmal1 in cardiomyocytes for mice with or without the ΔKPQ-Scn5a mutation increased the QT-interval at RR-intervals ≥ 130 ms. The prolongation in the QT-intervals was secondary to an increased slope factor of the QT- and RR-interval relation. Inducing the deletion of Bmal1 in the cardiomyocytes of mice with or without the ΔKPQ-Scn5a mutation also increased the rhythm-adjusted mean in the RR-interval, but it did not change the period, phase or amplitude. Compared to mice without the ΔKPQ-Scn5a mutation, mice with the ΔKPQ-Scn5a mutation had reduced heart rate variability (HRV) during the peak of the 24-hour RR-interval rhythm. Inducing the deletion of Bmal1 in cardiomyocytes did not affect HRV in mice without the ΔKPQ-Scn5a mutation but increased HRV in mice with the ΔKPQ-Scn5a mutation. The data demonstrate that deleting Bmal1 in cardiomyocytes of mice with the ΔKPQ-Scn5a mutation exacerbated the long QT-related phenotype.